2021
DOI: 10.33448/rsd-v10i4.13815
|View full text |Cite
|
Sign up to set email alerts
|

Z teste e tomada de decisão: Avaliação psicológica ideográfica para manuseio de arma de fogo

Abstract: A legislação brasileira atual sobre armamento estabelece normas que restringem o porte de arma no Brasil e torna obrigatória a realização de avaliação psicológica para aquisição e porte de arma de fogo. No Brasil, hoje, embora exista um perfil psicológico pré-definido pela Polícia Federal que orienta o psicólogo em sua tomada de decisão na avaliação psicológica para concessão de registro de arma de fogo, este aspecto carece de maior embasamento teórico. O objetivo deste estudo é traçar indicadores do Z teste p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…In this sense, it is observed that part of the compulsory context sample showed a tendency to be more emotionally unstable, immature and with a lower level of intellectual development, while another part showed a more mature and predictable performance in their emotional responses (Table 1). Among these TPC indicators, there are some of the variables that are associated with characteristics considered as counter-indicators for handling firearms, as described by Pellini (2006) andSá Hasbun et al (2021), and which are considered restrictive psychological indicators, according to IN 78/14 (Brasil, 2014), namely emotional instability, immaturity and low intellectual level. These characteristics correspond to those established in CFP Resolution No.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it is observed that part of the compulsory context sample showed a tendency to be more emotionally unstable, immature and with a lower level of intellectual development, while another part showed a more mature and predictable performance in their emotional responses (Table 1). Among these TPC indicators, there are some of the variables that are associated with characteristics considered as counter-indicators for handling firearms, as described by Pellini (2006) andSá Hasbun et al (2021), and which are considered restrictive psychological indicators, according to IN 78/14 (Brasil, 2014), namely emotional instability, immaturity and low intellectual level. These characteristics correspond to those established in CFP Resolution No.…”
Section: Discussionmentioning
confidence: 99%
“…Por isso, não é possível compará-las ou considerá-las como uma mesma avaliação. Ela pode ser identificada em contextos como o de trânsito (Aparecida, Mendes, & Silva, 2018), concursos públicos (Thadeu, Ferreira, & Faiad, 2012), cirurgia bariátrica (Walter, Hoyt, Martinez, & Dziura, 2021), porte de arma de fogo (Hasbun, Formiga, & Estevam, 2021;Rafalski & Andrade, 2015), reprodução assistida (Szöke et al, 2018), processo de transplantes de órgãos (Lazzaretti, 2006), aviação civil (Conselho Federal de Psicologia, 2019), entre outras aplicabilidades.…”
Section: Portación De Armas: Historia Y Desafíosunclassified